1992
DOI: 10.1088/0954-3899/18/4/006
|View full text |Cite
|
Sign up to set email alerts
|

Impact parameter dependence of collective flows and particle multiplicities in heavy-ion reactions

Abstract: AbslracLWe sludy the impact parameter dependence of mllective flows and panicle multiplicities in h e a y i o n reactions from 84-2100 MeV A -' . W e consider mainly the 'Oca +' ' Ca system. For mmparison with experimental data other synems are also considered. When the bombarding energies arc M o w 400 MeV A-', we use the quantum molecular dynamics (QMD) with the nucleon-nucleon moss seclion obtained from Ihe G-matrix. At bombarding energies in the GeV A-' region, we use relativislic quantum molecular dynamic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

1992
1992
1997
1997

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 62 publications
0
10
0
Order By: Relevance
“…In the non-relativistic Boltzmann-Uehling-Uhlenbeck (BUU) model, they found that in central heavy ion collisions at an incident energy of 0.7 GeV/nucleon the kaon yield obtained with a soft EOS (compressibility K=200 MeV) was about 2-3 times larger than that obtained with a stiff EOS (K=380 MeV). This finding was later confirmed in calculations based on the quantum molecular dynamics (QMD) [2,3].…”
mentioning
confidence: 70%
“…In the non-relativistic Boltzmann-Uehling-Uhlenbeck (BUU) model, they found that in central heavy ion collisions at an incident energy of 0.7 GeV/nucleon the kaon yield obtained with a soft EOS (compressibility K=200 MeV) was about 2-3 times larger than that obtained with a stiff EOS (K=380 MeV). This finding was later confirmed in calculations based on the quantum molecular dynamics (QMD) [2,3].…”
mentioning
confidence: 70%
“…Specifically, in-medium total as well as differential NN cross sections are needed by these models in dealing with the in-medium NN scattering using a Monte Carlo method. Moreover, if these models are used to calculate the spectrum of particles produced in heavy-ion collisions, such as photons, pions and kaons, one also needs to know the in-medium elementary particle production cross section [34,38,[42][43][44]; e.g., the in-medium cross section of neutron-proton (np) bremsstrahlung (np → npγ) is needed in the calculation of the photon production cross section in nucleus-nucleus collisions. Up till now, most calculations of particle production in nucleus-nucleus collisions are based on the free production cross sections.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it becomes possible to describe the time-development of totally anti-symmetrized wave functions [33,35]. These extended versions of the INC model are called microscopic transport models or microscopic simulations, and they have been successful in studying various aspects of heavy-ion collisions as well as light-ion induced reactions -particle production [36,37,21,19], single-particle spectra [23], collective flow [16,35], and fragment production [27,30,34,38]. This paper is organized as follows: We describe our INC model in Sec.…”
Section: Introductionmentioning
confidence: 99%